A mechanistic investigation of fuel oxidation reactions on the solid oxide fuel cell electrodes by using palladium catalyst nanoparticles - Alireza Babaei (2011)
A solid oxide fuel cell (SOFC) is a solid device for electrochemically converting the chemical energy of a fuel into electrical energy without conventional combustion of the fuel. SOFCs have several advantages over other types of fuel cells, including high conversion efficiency, low sensitivity to impurities in fuels and fuel flexibility. The high operating temperature (600-1000ºC) of SOFCs enables the use of not only hydrogen but also hydrocarbons as fuels. Direct utilization of hydrocarbon fuels without pre-reforming greatly reduces the complexity and cost of fuel cell systems. The imperative for direct use of hydrocarbons is the anode materials that should have high catalytic activity for hydrocarbon oxidation reactions and, at the same time, high resistance and tolerance towards the formation of coke and sulfur poisoning on the electrode surfaces. The performance of a SOFC can be improved significantly by addition of a catalyst to the electrodes. The objective of this PhD research is to investigate the mechanisms and kinetics of chemical and electrochemical reactions occurring over SOFC electrodes catalyzed by palladium (Pd) nano particles with the emphasis on the hydrocarbon oxidation reactions. For this purpose the Pd nano particles were introduced into the microstructures of the Ni/GDC and LCCM/GDC anode and LSM cathode electrodes of the SOFCs. The loading of the Pd nano particles was incrementally increased in the microstructures of the electrodes by using a wet impregnation technique. The effects of the presence of Pd nano particles on the oxidation reactions of hydrogen, methane, methanol and ethanol over the anodes and the oxygen reduction reactions over the cathodes were investigated by means of various analytical techniques including electrochemical methods over a temperature range of 650-900ºC.